Trust, Identity, and Public-Sphere Pro-environmental Behavior in China: An Extended Attitude-Behavior-Context Theory - Xing, Yunfeng; Li, Mengqi; Liao, Yuanhong (Frontiers in Psychology, 2022)
Changing human behavior is critical to mitigating the increasingly severe environmental harm. Although numerous studies focus on private-sphere or generalized pro-environmental behavior (PEB), relatively little research examines explicitly public-sphere PEB from a collective action perspective. This study incorporates trust and identity into the Attitude-Behavior-Context (ABC) theory to investigate Chinese residents’ participation in public-sphere PEB. Primary data collected from 648 residents in China tested the model empirically. The results indicate that social trust, environmentalist self-identity, and politicized identity positively predict public-sphere PEB and that institutional trust positively impacts non-activist behaviors but negatively relates to environmental activism. There is also evidence that trust and identity are moderators of attitude and public-sphere PEB. Specifically, social trust and environmentalist self-identity strengthen the effect of attitude on public-sphere PEB. Politicized identity increases the impact of attitude on environmental activism but not on non-activist behaviors, and there is no significant moderating effect of institutional trust. The findings deepen the understanding of public-sphere PEB and make more targeted policies accordingly.